Glycolysis and the pentose phosphate pathway are differentially associated with the dichotomous regulation of glioblastoma cell migration versus proliferation - Kathagen-Buhmann, Annegret; Schulte, Alexander; Weller, Jonathan; Holz, Mareike; Herold-Mende, Christel; Glass, Rainer; Lamszus, Katrin (Neuro-Oncology, 2016)
AbstractBackground. The dichotomy between glioblastoma cell migration and proliferation is regulated by various parameters including oxygen tension. In gliobla
Advance access date 24 February 2016
Gesehen am 07.05.2020